UV-C transparent glass and glass parts
A tailored aluminoborosilicate glass composition addresses meltability, thermal expansion, and water resistance issues, enhancing UV-C transmission and durability for UV-C LED packages.
Patent Information
- Application Number
- JP2024172781
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-10-01
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2044-10-01
AI Technical Summary
Existing UV-C transparent glasses face challenges in meltability, thermal expansion, and water resistance, which are crucial for UV-C LED packages, as they affect productivity, durability, and UV-C transmission efficiency.
A specific composition of aluminoborosilicate glass with SiO2, B2O3, Al2O3, Li2O, Na2O, K2O, R2O, MgO, CaO, SrO, BaO, Sb2O3, F, and Cl, with a balanced (R2O+R’O)/(SiO2+B2O3+Al2O3) ratio less than 0.1, ensuring good meltability, low thermal expansion, and excellent water resistance.
The solution provides UV-C transparent glass with improved meltability, low thermal expansion, and enhanced water resistance, ensuring high UV-C transmission and durability, suitable for precision mold press forming and UV-C LED applications.
Smart Images

Figure 0007602843000001 
Figure 0007602843000002 
Figure 0007602843000003
Abstract
Description
[Technical field]
[0001] The present invention relates to UV-C transmitting glass and glass components. [Background technology]
[0002] Conventionally, low-pressure mercury lamps emitting 184.9 nm and 253.7 nm ultraviolet light have been used as light sources for sterilization. However, the Minamata Regulation on Mercury, an international treaty concluded in 2013, prohibits the manufacture, import and export of mercury-containing products, except for some exemptions, from 2021. For this reason, there has been growing expectation for UV-C LEDs (deep ultraviolet LEDs), which have a low burden on the human body and the environment, as an alternative to low-pressure mercury lamps. Then, triggered by the spread of the COVID-19 infection, there has been an increased need to disinfect objects that an unspecified number of people touch on the spot, and UV-C LEDs, which are easy to use and compact, have rapidly spread into a new market.
[0003] However, while the output of each mercury lamp is several watts to several tens of watts, the output of each UV-C LED is several mW to several tens of mW. Therefore, in terms of output, UV-C LEDs are still in the development stage. In the future, as the efficiency of electrical and photovoltaic power generation increases and the output of UV-C LEDs exceeds 100 mW, UV-C LEDs will have an extremely strong sterilizing effect and will be able to be installed in large UV-C devices that have previously been used by mercury lamps.
[0004] As UV-C LEDs become more powerful, UV-C LED packages are required to be durable. UV-C LED packages use window members in the shape of a flat plate or lens. The lens-shaped window member protects the UV-C LED chip from the outside air, and also controls the light emitted from the UV-C LED, allowing for efficient UV-C irradiation.
[0005] Quartz glass, which has excellent UV-C transparency and durability, has been considered suitable as the glass used for the window material of UV-C LED packages. However, to manufacture quartz glass, the raw material needs to be melted at 2000°C or higher. In addition, processing of quartz glass requires mechanical processing such as cutting and polishing from an ingot. Therefore, quartz glass has problems with productivity and processability.
[0006] On the other hand, aluminoborosilicate glass has a lower melting temperature than quartz glass and has a high transmittance over a wide wavelength range, making it a useful glass for UV-C LED packages.
[0007] For example, Patent Documents 1 to 4 disclose aluminoborosilicate glasses that are transparent to ultraviolet light. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 4-342437 [Patent Document 2] JP 2018-197190 A [Patent Document 3] JP 2012-140314 A [Patent Document 4] JP 2013-230952 A Summary of the Invention [Problem to be solved by the invention]
[0009] From the viewpoint of productivity, it is essential that UV-C transmitting glass has good meltability. However, the glass disclosed in Patent Document 1 has poor meltability, and the production of the glass may require melting the raw materials at high temperatures. Furthermore, poor meltability leads to poor bubble removal, and bubbles may remain inside the glass. In addition, the glass disclosed in Patent Document 2 is particularly preferably made to contain 60 to 68 mass% of SiO2, which is the main component, and therefore there is a risk of poor meltability due to the large amount of SiO2.
[0010] It is essential that the UV-C transmitting glass has a low thermal expansion coefficient. For example, ceramics such as aluminum nitride (AlN) and alumina (Al2O3), which have high thermal conductivity, are usually used as the housing material for the package of a UV-C LED. Since the thermal conductivity of glass and ceramics is significantly different, when glass and a ceramic housing are bonded by applying heat, the temperature difference between the glass and the housing becomes large. Therefore, if the thermal expansion coefficient of glass is high, distortion occurs in the glass, which may cause breakage. However, Patent Documents 3 and 4 do not pay any attention to the thermal expansion coefficient.
[0011] UV-C transmitting glass is required to function as a sealant that protects the UV-C LED chip from moisture in the outside air, so it is also important that it has good water resistance. Furthermore, if the water resistance of the glass is poor, the glass may react with water, causing the glass to become cloudy, which may reduce the UV-C transmittance. However, Patent Documents 2 and 4 do not pay any attention to water resistance.
[0012] In view of the above, there is a need for UV-C transmitting glass that satisfies all of the requirements, particularly by optimizing the composition, including good melting properties, a low coefficient of thermal expansion, and excellent water resistance.
[0013] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide a UV-C transmitting glass that has good melting properties, a low thermal expansion coefficient, and excellent water resistance in a specific composition of aluminoborosilicate glass. Another object of the present invention is to provide a glass component using the above-mentioned UV-C transmitting glass. [Means for solving the problem]
[0014] Means of the Invention The present inventors have conducted extensive research to achieve the above object, and as a result have found that the above object can be achieved with a specific composition of aluminoborosilicate glass, thereby completing the present invention. The gist and configuration of the present invention to solve the above problems is as follows.
[0015] [1] In weight percent: SiO2: 46.90% or more and less than 55.00%, B2O3: more than 27.00% and less than 35.10%, Al2O3: 6.90% or more and 12.00% or less, Li2O: 0.90% or more and 8.00% or less, Na2O: 0.90% or more and 8.10% or less, K2O: 0% or more and 5.10% or less, R2O: 4.00% or more and less than 9.00% (wherein R2O represents the sum of Li2O, Na2O and K2O), MgO: 0% or more and 3.00% or less, CaO: 0% or more and 3.00% or less, SrO: 0% or more and 4.00% or less, BaO: 0% or more and 4.00% or less, R'O: 0% or more and less than 5.00% (wherein R'O represents the sum of MgO, CaO, SrO and BaO), Sb2O3: 0% or more and 1.00% or less, F: more than 0.01% and less than 1.00%, Cl: 0.05% or more and 1.00% or less Contains A UV-C transmitting glass characterized in that the mass ratio represented by (R2O+R'O) / (SiO2+B2O3+Al2O3) is less than 0.1.
[0016] [2] Average linear expansion coefficient (α 100-300℃ ) is 45 x 10 -7 / ℃ or more 60×10 -7 / °C or less.
[0017] [3] A UV-C transmitting glass according to [1] or [2], having an internal transmittance of 90% or more at a wavelength of 265 nm at a glass thickness of 1 mm.
[0018] [4] The UV-C transmitting glass according to any one of [1] to [3], which has a glass transition point of 510° C. or lower.
[0019] [5] A UV-C transmitting glass according to any one of [1] to [4], in which when a 20 mm x 10 mm x 10 mm glass piece is boiled in 1000 ml of pure water for 60 minutes, the weight loss rate before and after the boiling treatment is less than 0.1% by mass.
[0020] [6] The UV-C transmitting glass according to any one of [1] to [5], which is for precision mold press molding.
[0021] [7] A glass part, characterized in that the UV-C transmitting glass according to any one of [1] to [6] is used as a material. Effect of the Invention
[0022] According to the present invention, it is possible to provide a UV-C transmitting glass having good melting properties, a low thermal expansion coefficient, and excellent water resistance, in a specific composition of aluminoborosilicate glass. Furthermore, according to the present invention, it is possible to provide a glass component using the above-mentioned UV-C transmitting glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] (UV-C transparent glass) Hereinafter, a UV-C transmitting glass according to one embodiment of the present invention (hereinafter, sometimes referred to as "glass of this embodiment") will be specifically described. The glass of this embodiment is In mass%, SiO2: 46.90% or more and less than 55.00%, B2O3: more than 27.00% and less than 35.10%, Al2O3: 6.90% or more and 12.00% or less, Li2O: 0.90% or more and 8.00% or less, Na2O: 0.90% or more and 8.10% or less, K2O: 0% or more and 5.10% or less, R2O: 4.00% or more and less than 9.00% (wherein R2O represents the sum of Li2O, Na2O and K2O), MgO: 0% or more and 3.00% or less, CaO: 0% or more and 3.00% or less, SrO: 0% or more and 4.00% or less, BaO: 0% or more and 4.00% or less, R'O: 0% or more and less than 5.00% (wherein R'O represents the sum of MgO, CaO, SrO and BaO), Sb2O3: 0% or more and 1.00% or less, F: more than 0.01% and less than 1.00%, Cl: 0.05% or more and 1.00% or less One of its characteristics is that it contains (composition requirement). Furthermore, the glass of this embodiment is characterized in that the mass ratio represented by (R2O+R'O) / (SiO2+B2O3+Al2O3) is less than 0.1. The glass of this embodiment was discovered by the inventors through repeated experiments, and by satisfying the above compositional requirements and having a mass ratio represented by (R2O+R'O) / (SiO2+B2O3+Al2O3) less than 0.1, it is possible to provide a UV-C transmitting glass with good meltability, a low thermal expansion coefficient, and excellent water resistance in a specific aluminoborosilicate glass composition.
[0024] The reasons for limiting the range of each component in the composition requirements are as follows. Note that "%" for components means "% by mass" unless otherwise specified.
[0025] <sio2> SiO2 is an essential component in the glass of this embodiment, and is the main component that forms the network structure of the glass. SiO2 is a component that can reduce the thermal expansion coefficient and increase water resistance. Furthermore, SiO2 is a component that can increase the devitrification resistance stability. However, if the content of SiO2 is 55.00% or more, the viscosity of the glass melt increases, and there is a risk that the meltability will be significantly reduced. On the other hand, if the content of SiO2 is less than 46.90%, there is a risk that the effect of reducing the thermal expansion coefficient and the effect of increasing water resistance will not be sufficiently obtained. In addition, there is a risk that the effect of increasing the devitrification resistance stability will not be sufficiently obtained. Therefore, in the glass of this embodiment, the content of SiO2 is set to a range of 46.90% or more and less than 55.00%. From the same viewpoint, the content of SiO2 in the glass of this embodiment is preferably 47.00% or more, and is preferably 54.90% or less.
[0026] <b2o3> In the optical glass of this embodiment, B2O3 is a component that forms a glass network structure in the same way as SiO2. B2O3 is a component that can reduce the viscosity of the glass melt without changing the thermal expansion coefficient of the glass, and improve the meltability. Furthermore, B2O3 is a component that can improve the stability against devitrification. However, if the content of B2O3 exceeds 35.10%, there is a risk that the water resistance will deteriorate. On the other hand, if the content of B2O3 is 27.00% or less, there is a risk that the viscosity of the glass melt will increase, and the effect of improving the meltability will not be sufficiently obtained. Therefore, in the glass of this embodiment, the content of B2O3 is set to a range of more than 27.00% and 35.10% or less. From the same viewpoint, the content of B2O3 in the glass of this embodiment is preferably 27.50% or more, and preferably 35.05% or less.
[0027] <al2o3> In the glass of this embodiment, Al2O3 is a component that can reduce the thermal expansion coefficient of the glass and increase the water resistance of the glass. In addition, Al2O3 is a component that can suppress phase separation of the glass and increase the devitrification resistance stability. However, if the content of Al2O3 exceeds 12.00%, there is a risk that the meltability of the glass will deteriorate. On the other hand, if the content of Al2O3 is less than 6.90%, there is a risk that the effect of lowering the thermal expansion coefficient of the glass and increasing the water resistance of the glass cannot be sufficiently obtained. In addition, if the content of Al2O3 is less than 6.90%, there is a risk that the phase separation of the glass cannot be suppressed and the devitrification resistance stability will be significantly reduced. Therefore, in the glass of this embodiment, the content of Al2O3 is set to a range of 6.90% or more and 12.00% or less. From the same viewpoint, the content of Al2O3 in the glass of this embodiment is preferably 7.00% or more and preferably 11.80% or less.
[0028] <li2o> In the glass of this embodiment, Li2O is the component that reduces the viscosity of the glass melt the most among the alkali metal oxides and improves the meltability. However, if the content of Li2O exceeds 8.00%, the thermal expansion coefficient of the glass may increase. On the other hand, if the content of Li2O is less than 0.90%, the effect of reducing the viscosity of the glass melt and improving the meltability may not be sufficiently obtained. Therefore, in the glass of this embodiment, the content of Li2O is set to a range of 0.90% or more and 8.00% or less. From the same viewpoint, the content of Li2O in the glass of this embodiment is preferably 1.00% or more and preferably 7.80% or less.
[0029] <na2o> In the glass of this embodiment, Na2O is a component that reduces the viscosity of the glass melt and improves the meltability, although not as much as Li2O. However, if the content of Na2O exceeds 8.10%, the thermal expansion coefficient increases and the water resistance may be significantly deteriorated. On the other hand, if the content of Na2O is less than 0.90%, the effect of reducing the viscosity of the glass melt and improving the meltability may not be sufficiently obtained. Therefore, in the glass of this embodiment, the content of Na2O is set to a range of 0.90% or more and 8.10% or less. From the same viewpoint, the content of Na2O in the glass of this embodiment is preferably 1.00% or more and preferably 8.00% or less.
[0030] <k2o> In the glass of this embodiment, K2O is a component that reduces the viscosity of the glass melt and improves the meltability, although not as much as Li2O and Na2O. However, if the content of K2O exceeds 5.10%, there is a risk that the thermal expansion coefficient will become high. Therefore, in the glass of this embodiment, the content of K2O is set to a range of 0% or more and 5.10% or less. From the same viewpoint, the content of K2O in the glass of this embodiment is preferably 5.00% or less.
[0031] <r2o> R2O represents the sum of Li2O, Na2O and K2O. In the glass of this embodiment, the content of R2O is 4.00% or more and less than 9.00%. If the content of R2O is 9.00% or more, the thermal expansion coefficient of the glass may be high. On the other hand, if the content of R2O is less than 4.00%, the effect of reducing the viscosity of the glass melt and improving the meltability may not be sufficiently obtained. From the same viewpoint, the content of R2O in the glass of this embodiment is preferably 4.50% or more and preferably 8.97% or less.
[0032] <mgo> In the glass of this embodiment, MgO is a component that can increase the durability of the glass. However, if the content of MgO exceeds 3.00%, the melting property of the glass may deteriorate. Therefore, in the glass of this embodiment, the content of MgO is set to a range of 0% or more and 3.00% or less. From the same viewpoint, the content of MgO in the glass of this embodiment is preferably 2.50% or less.
[0033] <cao> In the glass of this embodiment, CaO is a component that can increase the durability of the glass. However, if the CaO content exceeds 3.00%, the melting property of the glass may deteriorate. Therefore, in the glass of this embodiment, the CaO content is set to a range of 0% or more and 3.00% or less. From the same viewpoint, the CaO content in the optical glass of this embodiment is preferably 2.50% or less.
[0034] <sro> In the optical glass of this embodiment, SrO is a component that can increase the stability against devitrification of the glass and can increase the durability of the glass. However, if the content of SrO exceeds 4.00%, the melting property of the glass may deteriorate. Therefore, in the glass of this embodiment, the content of SrO is set to a range of 0% or more and 4.00% or less. From the same viewpoint, the content of SrO in the optical glass of this embodiment is preferably 3.50% or less.
[0035] <bao> In the glass of this embodiment, BaO is a component that can increase the devitrification resistance stability of the glass and increase the durability of the glass. However, if the BaO content exceeds 4.00%, the melting property of the glass may deteriorate. Therefore, in the glass of this embodiment, the BaO content is set to a range of 0% or more and 4.00% or less. From the same viewpoint, the BaO content in the optical glass of this embodiment is preferably 3.50% or less.
[0036] <R’O> R'O represents the sum of MgO, CaO, SrO and BaO. In the glass of this embodiment, the R'O content is 0% or more and less than 5.00%. If the R'O content exceeds 5.00%, the meltability of the glass may deteriorate. From the viewpoint of further improving the durability and devitrification resistance of the glass, the R'O content in the optical glass of this embodiment is preferably 4.50% or less.
[0037] <sb2o3> In the glass of this embodiment, Sb2O3 is a component capable of degassing the glass melt and can be added as desired. When the content of Sb2O3 is 1.00% or less, the effect of degassing the glass melt can be sufficiently obtained. Therefore, in the glass of this embodiment, the content of Sb2O3 is set to a range of 0% or more and 1.00% or less.
[0038] <f> In the glass of this embodiment, F is a fining promoter. By adding a small amount of F (for example, more than 0.01%) to the glass, the glass is defoamed and fining is promoted. On the other hand, if the F content exceeds 1.00%, harmful fluorine volatiles are generated and may remain as bubbles in the glass. Therefore, in the glass of this embodiment, the F content is set to a range of more than 0.01% to 1.00%. Here, F can be contained in the glass by using fluorides such as KF, LiF, NaF, MgF2, CaF2, SrF2, BaF2, and AlF3 as raw materials.
[0039] <cl> In the glass of this embodiment, Cl is a fining promoter. When 0.05% or more of Cl is added to the glass, small bubbles expand and rise to the surface, fining is promoted. However, if the Cl content exceeds 1.00%, there is a risk of reducing the ultraviolet light transmittance. Therefore, in the glass of this embodiment, the Cl content is set to a range of 0.05% or more and 1.00% or less. Here, Cl can be contained in the glass by using chlorides such as KCl, LiCl, NaCl, AlCl3, MgCl2, CaCl2, SrCl2, and BaCl2 as raw materials.
[0040] <Mass ratio expressed as (R2O+R'O) / (SiO2+B2O3+Al2O3)> The glass of this embodiment requires that the mass ratio represented by (R2O+R'O) / (SiO2+B2O3+Al2O3) is less than 0.1. There is a risk that it is not possible to achieve both a low thermal expansion coefficient and excellent water resistance simply by satisfying the above-mentioned composition requirements. The glass of this embodiment can reliably reduce the thermal expansion coefficient by adjusting the content of components (R2O and R'O) that increase the thermal expansion coefficient and the content of components (SiO2, B2O3 and Al2O3) that decrease the thermal expansion coefficient or do not affect the thermal expansion coefficient, that is, by making the mass ratio represented by (R2O+R'O) / (SiO2+B2O3+Al2O3) less than 0.1. Therefore, the present invention can provide a UV-C transmitting glass that satisfies the above-mentioned composition requirements, and has a mass ratio expressed as (R2O+R'O) / (SiO2+B2O3+Al2O3) of less than 0.1, thereby exhibiting good meltability, a low thermal expansion coefficient, and excellent water resistance.
[0041] <fe2o3> Fe2O3 is a component that may absorb UV-C and deteriorate the transmittance of UV-C. However, it is very difficult to completely avoid contamination from glass raw materials or manufacturing processes, and glass usually inevitably contains Fe2O3. Therefore, the glass of this embodiment preferably has a low content of Fe2O3. Specifically, the glass of this embodiment preferably has a content of Fe2O3 of 0.01% or less, 0.005% or less, or 0.0005% or less. On the other hand, from the viewpoint of glass productivity, the glass of this embodiment preferably has a content of Fe2O3 of 0.00001% or more, or 0.0001% or more.
[0042] <tio2> Like Fe2O3, TiO2 is a component that may absorb UV-C and reduce the transmittance of UV-C. However, it is very difficult to completely avoid contamination from glass raw materials or manufacturing processes, and glass usually inevitably contains TiO2. Therefore, the glass of this embodiment preferably has a low TiO2 content. Specifically, the glass of this embodiment preferably has a TiO2 content of 0.02% or less, 0.015% or less, or 0.01% or less. On the other hand, from the viewpoint of glass productivity, the glass of this embodiment preferably has a TiO2 content of 0.0001% or more, or 0.0003% or more.
[0043] <Other ingredients> The glass of the present embodiment may contain other components other than the above-mentioned components (SiO2, B2O3, Al2O3, Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, Sb2O3, F, Cl, Fe2O3, TiO2) as long as the purpose is not exceeded. Examples of other components include Gd2O, Y2O3, La2O3, ZrO2, GeO2, Ta2O5, and P2O5. However, in order to more reliably exhibit the desired characteristics, the content of the other components in the glass of the present embodiment is preferably 5% or less, more preferably 3% or less, and even more preferably 1% or less, and it is particularly preferable that the glass of the present embodiment has a composition consisting of only the above-mentioned components. Here, "consisting only of the above-mentioned components" means that it does not substantially contain impurity components other than the above-mentioned components, specifically, the content of other components is 0.2% or less.
[0044] Cr2O3, NiO, CuO, CeO2, V2O5, WO3, MoO3, MnO2, and CoO are components that may absorb UV-C and reduce the transmittance of UV-C, so it is preferable that the glass of the present embodiment does not substantially contain these components.
[0045] Next, various characteristics of the glass of this embodiment will be described.
[0046] <meltability> In this specification, "meltability" refers to a phenomenon in which a vitrification reaction proceeds by heating homogeneously mixed blended raw materials at a melting temperature, resulting in a completely molten state without any unmelted material remaining. The glass of this embodiment has good meltability, so that the melting temperature is low and unmelted material and / or bubbles are unlikely to remain in the melt. For example, the glass of this embodiment can be obtained as homogeneous glass without unmelted material and / or bubbles by heating the blended raw materials of the glass of this embodiment in an electric furnace at a melting temperature of 1450°C for 3 hours.
[0047] <Thermal expansion coefficient> The thermal expansion coefficient is the average linear expansion coefficient (α 100-300℃ The average linear expansion coefficient is a physical property that indicates the rate at which an object's length changes in response to an increase in temperature, per unit of temperature, and is also called the thermal expansion coefficient. Since the glass of the present embodiment has a low thermal expansion coefficient, when heat is applied to a part of the glass and the temperature difference within the glass increases, the glass is less likely to be distorted and is less likely to crack due to heat. From the viewpoint of further reducing the thermal expansion coefficient of the glass, the glass of the present embodiment has an average linear expansion coefficient (α 100-300℃ ) is 60 x 10 -7 From the same viewpoint, the glass of the present embodiment preferably has an average linear expansion coefficient (α 100-300℃ ) is 59 x 10 -7 / °C or less. In addition, the glass of the present embodiment has an average linear expansion coefficient (α 100-300℃ ) is 45 x 10 -7 / °C or more, and 46×10 -7 It is more preferable that the temperature is 100° C. or higher.
[0048] In addition, the above-mentioned "average linear expansion coefficient (α 100-300℃ The "average linear expansion coefficient (α)" of the glass of the present embodiment is a value measured in accordance with JOGIS08-2019 "Method of measuring thermal expansion of optical glass" of the Japan Optical Glass Industry Association standard. 100-300℃ ) The adjustment of 」 can be carried out, for example, by appropriately adjusting the content of each component described above within a predetermined range and making the mass ratio represented by (R2O + R’O) / (SiO2 + B2O3 + Al2O3) less than 0.1.
[0049] <UV-C Transmittance> The glass of this embodiment has UV-C transmittance. The UV-C transmittance can be evaluated by measuring the internal transmittance at a wavelength of 265 nm with a glass thickness of 1 mm. Specifically, the glass of this embodiment can have an internal transmittance of 90% or more, and can also have an internal transmittance of 91% or more, at a wavelength of 265 nm with a glass thickness of 1 mm. The above-mentioned "internal transmittance" is obtained in accordance with the calculation formula of JOGIS 17-2019 "Method for Measuring the Internal Transmittance of Optical Glass" of the Japan Optical Glass Industry Association Standards. Also, the adjustment of the "internal transmittance" of the glass of this embodiment can be carried out, for example, by appropriately adjusting the content of each component described above within a predetermined range.
[0050] <Glass Transition Point> The glass of this embodiment preferably has a glass transition point of 510 °C or lower. The glass transition point is the temperature indicating the process from the melt to the glass, and is also a temperature serving as an index for judging the feasibility of mold forming. When the glass transition point becomes high, the molding temperature also becomes high, and there is a risk of problems such as the glass adhering to the mold used and being unable to be demolded. Therefore, it is preferably as low as possible, and in the glass of this embodiment, it is more preferably 500 °C or lower, and even more preferably 490 °C or lower.
[0051] The above-mentioned "glass transition point" refers to the temperature corresponding to the intersection of two tangents drawn from the low-temperature side and the high-temperature side of the bending part in the thermal expansion curve measured in accordance with JOGIS 08-2019 "Method for Measuring the Thermal Expansion of Optical Glass" of the Japan Optical Glass Industry Association Standards. Also, the adjustment of the "glass transition point" of the glass of this embodiment can be carried out, for example, by appropriately adjusting the content of each component described above within a predetermined range.
[0052] <Water resistance> Water resistance can be evaluated by calculating the weight loss rate. In this specification, the "weight loss rate" of glass refers to the weight loss rate (mass%) of a glass piece of 20 mm x 10 mm x 10 mm before and after boiling treatment in 1000 ml of pure water for 60 minutes. The weight loss rate is calculated from the following formula. Weight loss rate = ("mass of glass pieces before boiling treatment" - "mass of glass pieces after boiling treatment") x 100 / "mass of glass pieces before boiling treatment"
[0053] The glass of the present embodiment has excellent water resistance, and for example, the weight loss rate is preferably less than 0.1 mass %.
[0054] The "weight loss rate" of the glass of the present embodiment can be adjusted, for example, by appropriately adjusting the content of each of the above-mentioned components within a predetermined range.
[0055] (Production method of UV-C transmitting glass) Next, a method for producing the glass of the present embodiment will be described. Here, the glass of the present embodiment only needs to have the composition (content, mass ratio) of each component satisfying the above-mentioned range, and the manufacturing method thereof is not particularly limited, and the glass can be manufactured according to a conventional manufacturing method. For example, first, oxides, hydroxides, carbonates, nitrates, fluorides, chlorides, etc. are weighed in a predetermined ratio as raw materials of each component that can be contained in the optical glass of this embodiment, and mixed thoroughly to obtain a glass preparation raw material. Next, this glass preparation raw material is put into a melting vessel (e.g., a crucible of platinum group metal, platinum group metal alloy, quartz, etc.) that is not reactive with the glass preparation raw material, and heated to 1300 to 1450 ° C. in an electric furnace to melt, and stirred appropriately. Next, the mixture is clarified and homogenized in an electric furnace, cast into a mold preheated to an appropriate temperature, and then slowly cooled in an electric furnace to remove distortion, thereby producing the glass of this embodiment.
[0056] (Applications of UV-C transmitting glass) The use of the glass of the present embodiment is not particularly limited, but it is preferably for precision mold press molding. The glass of this embodiment also has an advantage in terms of mold forming, and by subjecting the glass of this embodiment to precision mold press forming, glass parts, which will be described later, can be easily manufactured.
[0057] (Glass parts) Hereinafter, a glass part according to one embodiment of the present invention (hereinafter, sometimes referred to as "the glass part according to the present embodiment") will be described. The glass component of this embodiment is characterized by using the above-mentioned UV-C transmitting glass as its material. Since the glass component of this embodiment uses the above-mentioned UV-C transmitting glass as its material, it has a low thermal expansion coefficient and excellent water resistance.
[0058] Examples of the glass parts of the present embodiment include, but are not limited to, LED cover lenses, lens arrays such as microlens arrays, prisms with lens functions, preform materials, fiber materials, etc. When the glass parts include lenses, the lenses may be spherical lenses, aspherical lenses, plano-concave lenses, plano-convex lenses, biconcave lenses, biconvex lenses, concave meniscus lenses, convex meniscus lenses, microlenses, lenses with diffraction gratings, rod lenses, etc. Furthermore, the lenses may be provided with an anti-reflection film, a wavelength-selective partial reflection film, etc. on their surfaces as necessary.
[0059] The method for producing the glass component of this embodiment is not particularly limited, and any known method can be appropriately selected depending on the purpose. For example, the glass component of this embodiment may be precision mold press molded. EXAMPLES
[0060] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0061] The glasses of the examples and comparative examples were produced by the following methods.
[0062] As the raw materials of each component in the compositions shown in Tables 1 to 8, the corresponding oxides, hydroxides, carbonates, nitrates, fluorides, chlorides, etc. were used, weighed to the desired ratio, and thoroughly mixed to obtain the blended raw materials. Next, the blended raw materials were put into a platinum crucible, melted in an electric furnace at a temperature of 1300 to 1450°C for several hours, and stirred with a platinum stirring rod at appropriate times to homogenize and clarify. After that, the mixture was cast into a mold preheated to an appropriate temperature, and then slowly cooled in an electric furnace to obtain the glass of each example. In each example, AlF3 was used as the fluoride, and NaCl was used as the chloride. In addition, the glass of each example had a Fe2O3 content of 0.01 mass% or less, and a TiO2 content of 0.02 mass% or less.
[0063] Comparative Examples 1 and 2 are examples corresponding to the compositions of Examples 1 and 4 described in Patent Document 1 (JP Patent Publication No. 4-342437), and Comparative Example 3 is an example corresponding to Example 1 in Patent Document 2 (JP Patent Publication No. 2018-197190). Comparative Examples 4, 5, and 6 are examples corresponding to Documents No. 1, 8, and 11 in Patent Document 3 (JP Patent Publication No. 2012-140314). Comparative Example 7 is an example corresponding to Example 1 in Patent Document 4 (JP Patent Publication No. 2013-230952).
[0064] For the obtained glasses of each example, the melting property, thermal expansion coefficient, water resistance, and UV-C transmittance were evaluated, and the glass transition point was measured, according to the following procedures. The results are shown in Tables 1 to 7, respectively.
[0065] <Evaluation of meltability> The meltability was evaluated by visual inspection after heating the mixed raw materials in an electric furnace at 1450°C for 3 hours, and then giving a grade of "A" if no unmelted material or bubbles were found, and a grade of "B" if unmelted material or bubbles were found.
[0066] <Evaluation of thermal expansion coefficient> The thermal expansion coefficient is evaluated by the average linear expansion coefficient (α 100-300℃ ) was measured. Specifically, the measurement of the average linear expansion coefficient (α 100-300℃ ) was carried out according to the method described in JOGIS 08 - 2019 "Method for Measuring Thermal Expansion of Optical Glass" of the Japan Optical Glass Industry Association Standard. The smaller the value of such average linear expansion coefficient (α 100-300℃ ), the lower (better) the thermal expansion rate.
[0067] <Evaluation of Water Resistance> As an evaluation of water resistance, the weight loss rate was calculated. Specifically, the calculation of the weight loss rate was carried out by the following method. The glass of each example was made into a glass piece of 20 mm × 10 mm × 10 mm, and the glass piece was boiled in 1000 ml of pure water for 60 minutes. Then, the weight loss rate was calculated by the following formula. The smaller the value of such weight loss rate, the more excellent the water resistance. Weight loss rate = ( "Mass of the glass piece before boiling treatment" - "Mass of the glass piece after boiling treatment" ) × 100 / "Mass of the glass piece before boiling treatment"
[0068] <Measurement of Glass Transition Point> The measurement of the glass transition point was carried out according to the method described in JOGIS 08 - 2019 "Method for Measuring Thermal Expansion of Optical Glass" of the Japan Optical Glass Industry Association Standard. The lower such glass transition point, the more excellent the moldability.
[0069] <Evaluation of UV - C Transmittance> As an evaluation of UV - C transmittance, the internal transmittance at a wavelength of 265 nm with a glass thickness of 1 mm was measured. Specifically, the calculation of the internal transmittance at a wavelength of 265 nm with a glass thickness of 1 mm was carried out according to the method described in JOGIS 17 - 2019 "Method for Measuring Internal Transmittance of Optical Glass" of the Japan Optical Glass Industry Association Standard. The larger the value of such internal transmittance, the more excellent the UV - C transmittance.
[0070]
Table 1
[0071]
Table 2
[0072] [Table 3]
[0073] [Table 4]
[0074] [Table 5]
[0075] [Table 6]
[0076] [Table 7]
[0077] [Table 8]
[0078] As shown in Tables 1 to 3, the glasses of Examples 1 to 20 according to the present invention were evaluated as having meltability of "A" and had an average linear expansion coefficient (α 100-300℃ ) is 60 x 10 -7 / °C or less, the weight loss rate was less than 0.10 mass%, and the internal transmittance at a wavelength of 265 nm at a glass thickness of 1 mm was 90% or more. These facts show that the glasses of Examples 1 to 20 have good meltability, low thermal expansion coefficients, excellent water resistance, and excellent UV-C transmittance.
[0079] Moreover, the glasses of Examples 1 to 20 had glass transition points of not more than 510° C. This shows that the glasses of Examples 1 to 20 are also advantageous in terms of molding.
[0080] On the other hand, as can be seen from Tables 4 to 8, the glasses of Comparative Examples 1 to 33 do not satisfy any of the ranges specified in the present invention, and therefore have poor meltability, high thermal expansion coefficients, and / or poor water resistance.
[0081] The meltability of the glass of Comparative Example 1 was evaluated as "B." This is believed to be due to the high SiO2 content and the low B2O3 content.
[0082] The meltability of the glass of Comparative Example 2 was evaluated as "B." This is believed to be due to the low content of B2O3.
[0083] Furthermore, the glasses of Comparative Examples 1 and 2 had low internal transmittance [%] at a wavelength of 265 nm at a glass thickness of 1 mm. This is believed to be because the glasses of Comparative Examples 1 and 2 had poor melting properties, and unmelted material and bubbles remained in the glass.
[0084] The glass of Comparative Example 3 was evaluated as having a melting property of "B" and an average linear expansion coefficient (α 100-300℃ ) was high. The glass of Comparative Example 3 also had a high glass transition point. This is believed to be due to the high contents of SiO2 and Na2O and the mass ratio represented by (R2O+R'O) / (SiO2+B2O3+Al2O3) being 0.1 or more.
[0085] The glass of Comparative Example 4 had an average linear expansion coefficient (α 100-300℃ This is believed to be due to the mass ratio (R2O+R'O) / (SiO2+B2O3+Al2O3) being 0.1 or more.
[0086] The glass of Comparative Example 5 was evaluated as having a melting property of "B" and an average linear expansion coefficient (α 100-300℃ ) was high. The glass of Comparative Example 5 had a high glass transition point. This is believed to be due to the high SiO2 content and the mass ratio represented by (R2O+R'O) / (SiO2+B2O3+Al2O3) being 0.1 or more.
[0087] The glasses of Comparative Examples 6 and 7 had an average linear expansion coefficient (α 100-300℃ This is believed to be due to the mass ratio (R2O+R'O) / (SiO2+B2O3+Al2O3) being 0.1 or more.
[0088] The glasses of Comparative Examples 8 to 25 have a mass ratio represented by (R2O+R'O) / (SiO2+B2O3+Al2O3) of less than 0.1, but the contents of any of the components in the glasses do not satisfy the ranges of each component in the composition requirements.
[0089] The glass of Comparative Example 8 had a large weight loss rate. This is believed to be due to the low SiO2 content and the high B2O3 content.
[0090] The glass of Comparative Example 9 had a particularly large weight loss. In addition, the glass of Comparative Example 9 experienced phase separation, and the internal transmittance [%] at a wavelength of 265 nm in a glass thickness of 1 mm was almost 0. These were believed to be due to the Al2O3 content being too low.
[0091] The glass of Comparative Example 10 had a large weight loss rate. This is believed to be due to the low content of Al2O3.
[0092] The meltability of the glasses of Comparative Examples 11 to 13 was evaluated as B. This is believed to be due to the high content of Al2O3.
[0093] The meltability of the glass of Comparative Example 14 was evaluated as "B." This is believed to be because the glass of Comparative Example 14 did not contain Li2O.
[0094] The meltability of the glass of Comparative Example 15 was evaluated as "B." This is believed to be because the glass of Comparative Example 15 does not contain Li2O and has a low Na2O content. Furthermore, the glass of Comparative Example 15 had a low internal transmittance [%] at a wavelength of 265 nm at a glass thickness of 1 mm. This is believed to be because the glass of Comparative Example 15 had poor melting properties and unmelted material and bubbles remained in the glass.
[0095] The glass of Comparative Example 16 had an average linear expansion coefficient (α 100-300℃ ) was high. This is thought to be due to the high content of K2O.
[0096] The meltability of the glass of Comparative Example 17 was evaluated as "B." This is believed to be due to the low content of R2O.
[0097] The glasses of Comparative Examples 18 and 19 had an average linear expansion coefficient (α 100-300℃ This is believed to be due to the high Li2O content and low Na2O content.
[0098] The glass of Comparative Example 20 had an average linear expansion coefficient (α 100-300℃ ) was high. This is thought to be due to the low Li2O content and the high Na2O content.
[0099] The glass of Comparative Example 21 had an average linear expansion coefficient (α 100-300℃ ) and the weight loss rate was large. This is thought to be due to the absence of Li2O and the high content of Na2O.
[0100] The meltability of the glass of Comparative Example 22 was evaluated as "B," which is believed to be due to the high content of MgO.
[0101] The meltability of the glass of Comparative Example 23 was evaluated as "B," which is believed to be due to the high CaO content.
[0102] The meltability of the glass of Comparative Example 24 was evaluated as "B," which is believed to be due to the high SrO content.
[0103] The meltability of the glass of Comparative Example 25 was evaluated as "B," which is believed to be due to the high content of BaO.
[0104] The glass of Comparative Example 26 had an average linear expansion coefficient (α 100-300℃ ) and the weight loss rate was large. This is thought to be due to the high R2O content and the mass ratio expressed as (R2O+R'O) / (SiO2+B2O3+Al2O3) being 0.1 or more.
[0105] The glass of Comparative Example 32 had an average linear expansion coefficient (α 100-300℃ This is believed to be due to the high R2O content and the mass ratio (R2O+R'O) / (SiO2+B2O3+Al2O3) being 0.1 or more.
[0106] The glasses of Comparative Examples 27 to 31 and 33 satisfy the composition requirements, but have a mass ratio represented by (R2O+R'O) / (SiO2+B2O3+Al2O3) of 0.1 or more. The glasses of Comparative Examples 27 to 31 all have an average linear expansion coefficient (α 100-300℃ ) was high. In addition, the glass of Comparative Example 33 had a large weight loss rate. From these facts, it is understood that even if the composition requirements are satisfied, when the mass ratio represented by (R2O+R'O) / (SiO2+B2O3+Al2O3) is 0.1 or more, it is not possible to achieve both a low thermal expansion coefficient and excellent water resistance. [Industrial Applicability]
[0107] According to the present invention, it is possible to provide a UV-C transmitting glass having good melting properties, a low thermal expansion coefficient, and excellent water resistance, in a specific composition of aluminoborosilicate glass. Furthermore, according to the present invention, it is possible to provide a glass component using the above-mentioned UV-C transmitting glass. < / cl> < / f> < / bao> < / sro> < / cao> < / mgo>
Claims
1. In mass percent, SiO 2 : 46.90% or more but less than 55.00%, B 2 O 3 : more than 27.00% and less than 35.10%, A 2 O 3 :6.90% or more and 12.00% or less, Li 2 O: 0.90% or more and 8.00% or less, Na 2 O: 0.90% or more and 8.10% or less, K 2 O: 0% or more and 5.10% or less, R 2 O: 4.00% or more and less than 9.00% (however, R 2 O is Li 2 O, Na 2 O and K 2 ), MgO: 0% or more and 3.00% or less, CaO: 0% or more and 3.00% or less, SrO: 0% or more and 4.00% or less, BaO: 0% or more and 4.00% or less, R'O: 0% or more and less than 5.00% (wherein R'O represents the sum of MgO, CaO, SrO and BaO); Sb 2 O 3 :0% or more and 1.00% or less, F: more than 0.01% and less than 1.00%, Cl: 0.05% or more and 1.00% or less Contains (R 2 O+R'O) / (SiO 2 +B 2 O 3 +Al 2 O 3 ) is less than 0.
1.
2. Average linear expansion coefficient (α 100-300℃ ) is 45 x 10 -7 / ℃ or more 60 x 10 -7 2. The UV-C transmitting glass according to claim 1, wherein the UV-C transmitting glass has a temperature of 100° C. or less.
3. 3. The UV-C transmitting glass according to claim 1, wherein the internal transmittance at a wavelength of 265 nm at a glass thickness of 1 mm is 90% or more.
4. 3. The UV-C transmitting glass according to claim 1, which has a glass transition point of 510° C. or lower.
5. 3. The UV-C transmitting glass according to claim 1, wherein when a glass piece of 20 mm × 10 mm × 10 mm is boiled in 1000 ml of pure water for 60 minutes, the weight loss rate before and after the boiling treatment is less than 0.1 mass %.
6. 3. The UV-C transmitting glass according to claim 1, which is for precision mold press molding.
7. A glass part, characterized in that the UV-C transmitting glass according to claim 1 or 2 is used as a material.
Citation Information
Patent Citations
Ultraviolet light transmitting glass
JP1985077144A
UV transmitting glass
JP1990141438A
Ultraviolet ray transmitting glass
JP1992342437A
Optical glass
JP2012140314A
Ultraviolet-visible region transmitting glass
JP2013230952A
Cited By
Ultraviolet-visible transmitting glass
WO2026164207A1
